تأثير استخدام تدريبات المطاولة الهوائية بطريقتي (تناوب السرعة والفتري منخفض الشدة) في عدد من المتغيرات الوظيفية والإنجاز في عدو 1500 متر - غفوری, ریباز بایز توفیق (Sulaimani Journal for Humanities, 2023)
The research aims to: - Detect the effect of using aerobic training by continuous training by alternating speed and low-intensity interval training on a number of functional variables (heart rate, number of breathing times, and oxygen saturation in the body). - Detection of the effect of using the air by continuous training by alternating speed and low-intensity interval training in achieving a 1500-meter run. - Detecting the significance of differences in a number of functional variables (heart rate, number of respirations, and oxygen saturation in the body) and the completion of a 1500-meter run between the two experimental research groups after implementing the two methods of continuous training with alternating speed and low-intensity interval training in the post-test. As for the research hypotheses: the two training curricula using continuous training with alternating speed and low-intensity interval positively affect the functional variables (heart rate, number of respirations, and oxygen saturation in the body) and achievement in the 1500-meter run. There are statistically significant differences between the two experimental research groups in a number of functional variables (heart rate, number of respirations, and oxygen saturation in the body) and achievement in the 1500-meter run in the post-test. The researcher used the experimental approach due to its suitability to the nature of the research, and it included (40) students from the fourth stage students in the College of Physical Education / Koya University. Two proposed training programs were designed and standardized in terms of the intensity used and its percentage for each type of exercise and the distances used in units, totals, repetitions and rest periods, by following up on scientific sources and references. Then, the results of the study were analyzed using the spss statistical package to find out the level of statistical significance. The results of this study reached 1. The training program that was carried out by the first experimental group that used continuous load training with alternating speed developed in achieving the 1500-meter sprint. 2. The training program that was carried out by the second experimental group, which used low-intensity interval training, made progress in achieving the 1500-meter sprint. 3. Despite the development that occurred for the two groups in completing the 1500-meter run, the results did not show significant differences between the two research groups in the post-test. 4. The training program that was implemented in the first experimental group that used continuous load training with alternating speed caused a decrease in the resting pulse rate and a rise after the 1500-meter run, and the program also caused a significant development in the heart rate (immediately after the effort, after one minute, after 3 minutes). The pulse rate after 5 minutes did not rise to the level of significance.